Lead Adsorption in Aqueous Solution by Giant Mimosa Pods Treated with NaOH - คะเณมา ดร.ปิยนุช (Journal of Food Health and Bioenvironmental Science, 2016)
This research aimed to study the potential of lead adsorption in aqueous solution by using 1.5 M NaOH-treated giant mimosa pods, comparing these with untreated pods. Batch experiment was carried out to investigate the effect of experimental parameters such as adsorbent dose, contact time, pH solution and initial lead concentration, and Langmuir and Freundlich isotherm were used to analyze the equilibrium adsorption. The findings found that the pretreatment could reduce adsorbent dose and increase an adsorbing potential on the initial lead concentration (5 mg/l) with the optimal contact time at 15 min and pH solution at 5. According to isotherm study, it fit to a monolayer adsorption explanation by the Langmuir equation. The pretreatment enhanced the maximum adsorption capacity over than the untreated treatment (2.05 > 1.34 mg/g).